(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
Ectopic pregnancy is a diagnosis that is quite challenging to make. It has been estimated that 40% of ectopic pregnancies go undiagnosed on initial presentation. Ectopic pregnancy is also a very difficult condition to identify based on history and physical, with both the history and physical examination features being neither sensitive nor specific for the diagnosis. Data suggests that even experienced gynecologists are unable to detect more than half of the masses created by ectopic pregnancy on physical exam. Due to these nature of the condition, laboratory data and diagnostic imaging are essential components of diagnosing ectopic pregnancy. Ultrasonography is the diagnostic imaging study of choice for ectopic pregnancy. Even if an ectopic pregnancy cannot be visualized on ultrasound, diagnosing an intrauterine pregnancy greatly reduces the risk of an ectopic pregnancy being present. This activity reviews ectopic pregnancy and highlights the role of the interprofessional team in evaluating and treating patients with this condition.